Best Answer

7x3 + 2x = 60

7x3 + 2x - 60 = 0

7x3 - 28 x + 30x - 60 = 0

7x(x2 - 4) + 30(x - 2) = 0

7x(x + 2)(x - 2) + 30(x - 2) = 0

(x - 2)[7x(x + 2) + 30] = 0

(x - 2)(7x2 + 14x + 30) = 0

x - 2 = 0 or 7x2 + 14x + 30 = 0

x = 2 or

x = {-14 +&- square root of [142 - 4(7)(30)]}/(2)(7)

x = -14/14 +&- (square root of -644)]/14

x = -1 +&- 2i(square root of 161)/14

x = -1 +&- (square root of 161)i/7

Q: What is 7x cubed plus 2 x equals 60?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

X=4.2666666666667

x = 4 You have to add the 8x and 7x to get 15x and then divide 60 by 15 to get x by itself.

7x - 4 = 60 7x = 64 x = 9.14

-46 = 3x + 7x

13x

Related questions

X=4.2666666666667

x = 4 You have to add the 8x and 7x to get 15x and then divide 60 by 15 to get x by itself.

7x + 10 = -7x - 60 Add 7x to both sides: 14x + 10 = -60 Subtract 10 from both sides: 14x = -70 Divide both sides by 14: x = -5

if its x(squared) its 7x(cubed) if its 2xX its 14x(squared)

7x - 4 = 60 7x = 64 x = 9.14

-46 = 3x + 7x

-3

7x + y = 8 Subtract 7x from each side of the equation: y = -7x + 8

[ x3 - 4x2 + 7x ] / (x) = x2 - 4x + 7

13x

x=6

It is 9x